2016
DOI: 10.1080/15384101.2016.1191709
|View full text |Cite
|
Sign up to set email alerts
|

Forced KLF4 expression increases the generation of mature plasma cells and uncovers a network linked with plasma cell stage

Abstract: A role of the transcription factor Kr€ uppel-like factor 4 (KLF4) in the generation of mature plasma cells (PC) is unknown. Indeed, KLF4 is critical in controlling the differentiation of various cell linages, particularly monocytes and epithelial cells. KLF4 is expressed at low levels in pro-B cells and its expression increases as they mature into pre-B cells, resting na€ ıve B cells and memory B cells. We show here that KLF4 is expressed in human bone marrow plasma cells and its function was studied using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Gefitinib can induce apoptosis by activating the caspase cascade in NSCLC cells carrying the sensitive mutation of EGFR . Krüppel‐like factor 4 also has an ambiguous apoptosis‐induced effect in bladder cancer cells, breast cancer cells, and plasma cells . The present study revealed that knockdown of KLF4 promoted gefitinib‐induced apoptosis by upregulating expression of apoptosis‐related proteins in c‐Met‐overexpressing NSCLC cells (Figure A,C) but not in NSCLC cells without c‐Met overexpression (Figure ), whereas overexpression of KLF4 suppressed gefitinib‐induced apoptosis in gefitinib‐sensitive cells (Figure B,D).…”
Section: Discussionmentioning
confidence: 48%
“…Gefitinib can induce apoptosis by activating the caspase cascade in NSCLC cells carrying the sensitive mutation of EGFR . Krüppel‐like factor 4 also has an ambiguous apoptosis‐induced effect in bladder cancer cells, breast cancer cells, and plasma cells . The present study revealed that knockdown of KLF4 promoted gefitinib‐induced apoptosis by upregulating expression of apoptosis‐related proteins in c‐Met‐overexpressing NSCLC cells (Figure A,C) but not in NSCLC cells without c‐Met overexpression (Figure ), whereas overexpression of KLF4 suppressed gefitinib‐induced apoptosis in gefitinib‐sensitive cells (Figure B,D).…”
Section: Discussionmentioning
confidence: 48%
“…It was recently shown that KLF4 enhances memory B-cells differentiation into early plasma cell and long lived plasma cells (111113). …”
Section: Physiological Functions In Tissues and Organsmentioning
confidence: 99%
“…This hypoxic microenvironment is important for normal bone marrow hematopoiesis. We investigated the impact of decreased oxygen partial pressures in plasma cell generation using our in vitro model 3,6,11,12 at each step (day 4, day 7 and day 10) of B cell differentiation (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%